DOCUMENT CIRCULATION, ACCOUNTING AND CONTROL OF CASH TRANSACTIONS (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the circulation, accounting, and control of cash receipt operations, which are essential processes in financial and economic activities. The paper delves into the basics of cashless payments and their organization, emphasizing the key documents involved in the process. Specifically, it focuses on the processing and accounting of payment orders and payment demands. The article examines how these operations are carried out in practice, highlighting the importance of properly organizing them for efficient financial management and control. Furthermore, the challenges and potential issues in the execution of these operations are discussed, along with recommendations for improving the effectiveness of the management system.